HUBUNGAN STATUS GIZI DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI 063 DI PESISIR SUNGAI SIAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Muchlis "; Yanti Ernalia; Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNutrition is an important factor in the development of human resources (HR) to form a healthy and productive human resources. The child is a human asset and future generations to consider life, particularly in terms of nutritional status, nutrition contained in various types of food is very important in maintaining the growth and development of the human body. Good nutritional status will affect the child's achievement and good concentration. This study aimed to determine the nutritional status anata relationship with student achievement 063 public elementary schools in coastal rivers Siak District of Rumbai coastal city of Pekanbaru. This research was conducted with a cross-sectional design of the 93 students. The study was conducted from April to September 2015. This study used proportionate stratified random sampling technique. Data obtained by measuring the nutritional status anthropometric indicators of TB / U is then compared with the CDC chart 2000 and acquired learning achievements of the student report card. The results showed most of the nutritional status of students is normal for 74.2% and most of the learning achievement is low at 53.8%. Data analysis using Chi-square test showed no association between nutritional status and student achievement with p value = 0.771.Keywords : Nutritional state, Learning achievment